Pelatihan Pengelolaan Drainase Lingkungan bagi Masyarakat dalam Mengatasi Banjir di Desa Sipungguk - Desrimon, Arfi; Islah, Muhammad; Islami, Fajril (Journal of Social and Community Service, 2024)
This community service activity aims to empower the community of Sipungguk Village, Salo District, Kampar Regency, in the drainage management system to reduce the risk of flooding. The main problems faced include poor drainage function, blockages due to garbage, lack of routine maintenance, suboptimal planning, low public awareness of the importance of drainage, and declining air quality due to inappropriate systems. The implemented solutions include increasing drainage capacity and planning, better waste management, regular maintenance, the implementation of environmentally friendly systems, increasing public awareness through outreach, and more integrated air management. The implementation methods include field surveys, interviews, policy analysis, and collaboration with the village government, NGOs, the private sector, and the local community. The results of the activity show that active community involvement in the planning, implementation, and maintenance of drainage can increase environmental awareness, reduce waterlogging during rain, and strengthen cooperation between related parties. This program is expected to become a model that can be applied in other villages in order to realize effective, sustainable drainage management that has a positive impact on the environment and community welfare.